2023
DOI: 10.1002/eqe.3992
|View full text |Cite
|
Sign up to set email alerts
|

Shaking table tests on the seismic response of truss structure with air spring‐FPS three‐dimensional isolation bearing

Qinghua Han,
Ming Jing,
Yan Lu

Abstract: To investigate the isolation effect of the friction pendulum system (FPS) horizontal isolation bearing and the air spring‐FPS three‐dimensional (3D) isolation bearing in truss structure and the influences of long‐period ground motions on the isolated structure, the shaking table test of a truss structure is designed and conducted. The ordinary ground motions, near‐fault pulse‐like ground motions, and far‐field long‐period ground motions with different spectral characteristics are chosen to input into the struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The two kinds of ground motion were input into different peak accelerations for research. Their acceleration time history curves were as follows: the maximum acceleration and corresponding time of "1244" ground motion were Max = 0.333 g and T = 37.42 s, and the minimum acceleration and corresponding time were Min = −0.340 g and T = 36.97 s, as shown in Figure 5A [13]. The maximum acceleration and corresponding time of "960" ground motion were Max = 0.404 g and T = 4.69 s, and the minimum acceleration and corresponding time are Min = −0.267 g and T = 5.64 s, s shown in Figure 5B.…”
Section: Seismic Wave Loadingmentioning
confidence: 99%
See 1 more Smart Citation
“…The two kinds of ground motion were input into different peak accelerations for research. Their acceleration time history curves were as follows: the maximum acceleration and corresponding time of "1244" ground motion were Max = 0.333 g and T = 37.42 s, and the minimum acceleration and corresponding time were Min = −0.340 g and T = 36.97 s, as shown in Figure 5A [13]. The maximum acceleration and corresponding time of "960" ground motion were Max = 0.404 g and T = 4.69 s, and the minimum acceleration and corresponding time are Min = −0.267 g and T = 5.64 s, s shown in Figure 5B.…”
Section: Seismic Wave Loadingmentioning
confidence: 99%
“…The related content will be introduced [11,12]. Han et al [13] considered the influence of near-fault ground motion with different characteristics on the dynamic response of isolated structures, and the forward-directional effect velocity pulse, slip impact effect velocity pulse and no velocity pulse were inputted into the shaking table tests. Experimental results showed that the dynamic response of near-fault ground motion with pulses was significantly greater than that without pulses, and the response with pulses was related to the structural period.…”
Section: Introductionmentioning
confidence: 99%